2021
DOI: 10.3389/fevo.2021.693781
|View full text |Cite
|
Sign up to set email alerts
|

Starvation and Climate Change—How to Constrain Cancer Cell Epigenetic Diversity and Adaptability to Enhance Treatment Efficacy

Abstract: Advanced metastatic cancer is currently not curable and the major barrier to eliminating the disease in patients is the resistance of subpopulations of tumor cells to drug treatments. These resistant subpopulations can arise stochastically among the billions of tumor cells in a patient or emerge over time during therapy due to adaptive mechanisms and the selective pressures of drug therapies. Epigenetic mechanisms play important roles in tumor cell diversity and adaptability, and are regulated by metabolic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 145 publications
(201 reference statements)
1
2
0
Order By: Relevance
“…Both dynamic and stable forms of RAE could be important mechanisms in cancer. 75 Thus, our finding that hc-RAE in human tissues is significantly enriched in cancer pathways supports expanded studies of hc-RAE genes in oncogenesis, metastasis, and the evolution of drug resistance. Moreover, our methodology will enable direct profiling of RAE in tumor tissue samples to investigate these relationships, and previous work has shown that monoallelic expression is tumor and gene specific and an important predictor of cancer progression.…”
Section: Discussionsupporting
confidence: 76%
“…Both dynamic and stable forms of RAE could be important mechanisms in cancer. 75 Thus, our finding that hc-RAE in human tissues is significantly enriched in cancer pathways supports expanded studies of hc-RAE genes in oncogenesis, metastasis, and the evolution of drug resistance. Moreover, our methodology will enable direct profiling of RAE in tumor tissue samples to investigate these relationships, and previous work has shown that monoallelic expression is tumor and gene specific and an important predictor of cancer progression.…”
Section: Discussionsupporting
confidence: 76%
“…Korolev et al (2014) suggested that the cancer cells can be viewed as an endangered species, in order to exploit cancer vulnerabilities to drive its extinction, using the ecology of tumors for treatment [162]. Gregg (2021) combined knowledge from ecology, evolution, biochemistry, infectious disease, species extinction, metabolism, genomics and epigenetics to develop clinically relevant strategies to constrain cancer cell diversity and adaptability to enhance treatment efficacy in metastatic cancer by association of treatment with ecological factors, such as hyperthermia, fasting, and immunotherapy, similar to starvation and climate change in nature as factors that drive the extinction of species [163].…”
Section: Methods For Biomarkers Investigationmentioning
confidence: 99%
“…The integrated strategy was inspired by the insights from the ecological studies on habitat fragmentation, namely that habitat reduction along with stochasticity in mortality could trigger species extinction. Ewers and Didham, 2007;Adler and Gordon, 2019;Hansen and Read, 2020;Araujo et al, 2021;Dua et al, 2021;Gregg, 2021;Solé and Aguadé-Gorgorió, 2021 of constraining and changing environments (Hall, 2017). The cancer cell environment includes other host cells, microbiomes, and the biochemical and physiological environments.…”
Section: Key Concepts/hypotheses In Cancer Ecologymentioning
confidence: 99%